2021
DOI: 10.26832/24566632.2021.0604015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fertilizer doses on the production of Chaite-5 paddy variety in Dhanusha District, Nepal

Abstract: The application of inorganic nutrient sources is necessary for proper agricultural growth that can ensure high quality food production. A field experiment was carried out in Hansapur, Dhanusha from March 2021 to July 2021 to study the effect of different fertilizer doses on the growth and yield of rice. The experiment was set up in a randomized complete block design (RCBD) with 7 different treatments following three replications. The treatments were named as T1: Control, T2: RDF (Recommended dose of fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Several research studies have sought to rationalize N fertilization of rice globally, which has an impact on the production (Qichun & Guang-huo, 2002;Dai et al, 2003;Lassaletta et al, 2014) Adhikari et al (2021). reported that the highest rice yield in Nepal was observed in response RD and 125RD treatments, which is very much analogous to our study results.…”
supporting
confidence: 88%
“…Several research studies have sought to rationalize N fertilization of rice globally, which has an impact on the production (Qichun & Guang-huo, 2002;Dai et al, 2003;Lassaletta et al, 2014) Adhikari et al (2021). reported that the highest rice yield in Nepal was observed in response RD and 125RD treatments, which is very much analogous to our study results.…”
supporting
confidence: 88%
“…Due to the growing population in the country, the existing rice production is inadequate to meet the food requirements. To fulfil the growing food demand in the nation, it should be prioritized to increase productivity per unit area given the constraints on extending cultivable land (Adhikari et al, 2021). Nepal must increase its rice output by more than 6.0 million tons by 2020 to meet the demands of its growing population (Devkota et al, 2019).…”
Section: Introductionmentioning
confidence: 99%